Beyond the walls: The social reintegration of prisoners through the dialogic reading of classic universal literature in prison - García-Carrión, Rocío (International journal of offender therapy and comparative criminology, 2019)
This study analyzed whether it was possible to successfully transfer an experience of dialogic literary gatherings (DLGs) developed in a prison in the Basque Country (Spain), which was found to enhance the participants' readiness to return to their communities. A case study was conducted in a different prison in Catalonia that comprised interviews and focus groups with a group of female prisoners and volunteers involved in the DLG. The communicative analysis conducted showed that the replication of the DLG allowed the participants to discuss and reflect on their biographies and their expected pathways upon release, thus opening possibilities for personal and social change. The results show that participants perceived the DLG as a helpful resource for social reintegration and suggest that DLGs can be transferred to different correctional institutions